Transspinal stimulation increases motoneuron output of multiple segments in human spinal cord injury - Murray, Lynda M.; Knikou, Maria (PloS one, 2019)
Targeted neuromodulation strategies that strengthen neuronal activity are in great need for restoring sensorimotor function after chronic spinal cord injury (SCI). In this study, we established changes in the motoneuron output of individuals with and without SCI after repeated noninvasive transspinal stimulation at rest over the thoracolumbar enlargement, the spinal location of leg motor circuits. Cases of motor incomplete and complete SCI were included to delineate potential differences when corticospinal motor drive is minimal. All 10 SCI and 10 healthy control subjects received daily monophasic transspinal stimuli of 1-ms duration at 0.2 Hz at right soleus transspinal evoked potential (TEP) subthreshold and suprathreshold intensities at rest. Before and two days after cessation of transspinal stimulation, we determined changes in TEP recruitment input-output curves, TEP amplitude at stimulation frequencies of 0.1, 0.125, 0.2, 0.33 and 1.0 Hz, and TEP postactivation depression upon transspinal paired stimuli at interstimulus intervals of 60, 100, 300, and 500 ms. TEPs were recorded at rest from bilateral ankle and knee flexor/extensor muscles. Repeated transspinal stimulation increased the motoneuron output over multiple segments. In control and complete SCI subjects, motoneuron output increased for knee muscles, while in motor incomplete SCI subjects motoneuron output increased for both ankle and knee muscles. In control subjects, TEPs homosynaptic and postactivation depression were present at baseline, and were potentiated for the distal ankle or knee flexor muscles. TEPs homosynaptic and postactivation depression at baseline depended on the completeness of the SCI, with minimal changes observed after transspinal stimulation. These results indicate that repeated transspinal stimulation increases spinal motoneuron responsiveness of ankle and knee muscles in the injured human spinal cord, and thus can promote motor recovery. This noninvasive neuromodulation method is a promising modality for promoting functional neuroplasticity after SCI.